Abusing Constitutional Identity - Scholtes, Julian (German law journal, 2021)
Increasingly, populists and authoritarians have discovered for themselves the notion of constitutional identity as a practical excuse to sidestep transnational legal obligations, as well as to vindicate their constitutional projects on the whole from concerns about the rule of law and other shared European values. This has led some scholars to highlight the “dangers of constitutional identity,” brandishing it as an “inherently dangerous concept,” and suggesting that the concept ought to be abandoned. This Article argues that the anti-pluralist critiques of constitutional identity, while rightly criticizing the authoritarian appropriations of constitutional identity, ultimately go too far and draw the wrong conclusions. Simply dismissing the concept of constitutional identity will not lead to the disappearance of the meanings imparted through it. The authoritarian and populist appropriations of constitutional identity must be identified and understood as abuses of the concept. By eliding constitutional identity with its abuse, the anti-pluralist critique sacrifices a more intimate understanding of the realities of constitutional identity abuse to a likely unattainable normative vision of uncontested EU law primacy. In advancing this critique, I will further outline three potential avenues for understanding constitutional identity abuse, differentiating between its substantive, generative, and relational aspects. Constitutional identity claims can be abusive by virtue of their substantive content, how they have come about, as well as how they are advanced.